Parametric study of laser marking process using grey taguchi method utilizing fiber laser system for aisi 304 stainless steel - Mohd Noor Firdaus, Haron (2021)
The laser marking process is a laser-assisted material removing machining technique which utilize heat to remove the material. In laser marking process, the surface of material is heat up and subsequently vaporize the work piece. The study reviews the different laser marking procedure with various input parameters which are taken for different work piece materials. It is difficult to obtain and optimize the cross-relation between the design parameters with input factors that contribute to the output performance factor. This study parametrically optimizes the fiber laser marking parameters for stainless steel AISI 304. The purpose of study is to have marking's quality with short period of time prediction to ensure a lower cost optimization approached. With the use of Grey Taguchi method for the laser marking, different design parameters and input factors are possible to be optimized for better output performance. Design of experiment of the fiber laser marking process was conducted on AISI 304 stainless steel material. L9 orthogonal array was applied it means 9 set of laser marking samples setup were tested. The research applied frequency, marking speed and marking loop as input parameters while the output parameters were the surface roughness, indentation and material removal rate. Based on the design of experiment for the Grey Taguchi approach, an optimum fiber laser design parameters were calculated with the consideration of noise ratio factor. Various process response behaviors were taken into account for full spectrum of the fiber laser marking performance ability. By interpret the Grey Taguchi results, it was concluded that the best setup were at frequency 60 Hz., speed 800mm/s and mark loop at 30 times. It is concluded by verification test, the optimization setup shows a good laser marking performance. The effect of the input parameters were frequency is 33.11 %, marking speed is 24.79% and marking loop is 14.99 % for the optimized laser marking process.